2004
DOI: 10.1093/ps/83.8.1335
|View full text |Cite
|
Sign up to set email alerts
|

The effects of copper on the efficacy of phytase, growth, and phosphorus retention in broiler chicks

Abstract: Copper is often added to broiler diets at prophylactic concentrations as an antimicrobial despite purported chelation with and reduced utilization of phytin phosphorus. Therefore, male chicks were fed 0, 62.5, 125, 250, or 375 ppm Cu from Cu sulfate in combination with 600 phytase units (FTU)/kg phytase from 9 to 22 d of age (6 cages/diet, 8 birds/cage). Nonphytate phosphorus (NPP) and Ca were formulated to 0.2 and 0.7% of the diet, respectively. Three additional control diets were formulated to contain 0.27, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 18 publications
0
22
2
2
Order By: Relevance
“…Further Cu-supplementations from inorganic and/or organic sources did not significantly improve turkeys performance and health. Other authors (Guo et al, 2001;Banks et al, 2004a) reported also that copper source did not affect broiler performance. MIKULSKI D. ET AL.…”
Section: Discussionmentioning
confidence: 92%
“…Further Cu-supplementations from inorganic and/or organic sources did not significantly improve turkeys performance and health. Other authors (Guo et al, 2001;Banks et al, 2004a) reported also that copper source did not affect broiler performance. MIKULSKI D. ET AL.…”
Section: Discussionmentioning
confidence: 92%
“…However, Robbins and Baker (1980) and Banks et al (2004b) reported that supplementation of 250 mg/kg of Cu had no significant effect on broiler BW gain and feed conversion efficiency. Banks et al (2004a) noted that Cu supplementation with 250 mg/kg from Cu Sul decreased BW gain, feed consumption, and feed conversion efficiency. Although conflicting results about growth benefits of high dietary Cu on broilers have been reported, the poultry industry still adds high concentrations of Cu to diets as a growth promoter and for its purported bactericidal and bacteriostatic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies that correlate dietary phytase inclusion with phosphorus availability and bone deposition express their results as bone ash and phosphorus percentage and as bone strength (Banks et al, 2004;Payne et al, 2005;Pérsia & Saylor, 2006e Martinez et al, 2006, and suggest that the inclusion of phytase in diets with different available phosphorus levels promote higher ash content or tibia strength. Means followed by different letters in the same column are significantly different (p<0.05) by the test of Tukey.1 -ns -not significant ; ** -significant (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion of 250 FTU phytase/kg feed and no phytase supplementation (control treatment) promoted the best results. Onyango et al (2004) evaluated the inclusion of phytase in feeds based on corn and soybean meal with reduced phosphorus content in starter broilers, and observed that bone density, bone mineral content, bone strength, and ash percentage were positively influenced by dietary phytase supplementation.Most studies that correlate dietary phytase inclusion with phosphorus availability and bone deposition express their results as bone ash and phosphorus percentage and as bone strength (Banks et al, 2004;Payne et al, 2005; Pérsia & Saylor, 2006 e Martinez et al., 2006, and suggest that the inclusion of phytase in diets with different available phosphorus levels promote higher ash content or tibia strength. Means followed by different letters in the same column are significantly different (p<0.05) by the test of Tukey.1 -ns -not significant ; ** -significant (p < 0.01).…”
mentioning
confidence: 99%